A global line list for HDO between 0 and 35000 cm−1 constructed using multiphoton spectra. (September 2021) - Zobov, Nikolay F.; Koshelev, Maksim A.; Makarov, Dmitry S.; Makhnev, Vladimir Yu.; Boyarkin, Oleg V.; Tyuterev, Vladimir G.; Tennyson, Jonathan; Polyansky, Oleg L.
Highlights: Multiphoton spectra are used to measure 210 new HDO energy levels. An energy switching potential energy surface is constructed. HDO line list for infrared, visible and near ultraviolet spectra. Graphical abstract: Abstract: Multiphoton spectroscopy of monodeuterated water is employed to determine more than 210 new energy levels of HDO in the 25 000–35 000 cm − 1 region. These new empirical energy levels are used to fit a potential energy surface (PES) valid between 20 000 cm − 1 and 35 000 cm − 1 . Using this PES and an accurate lower energy PES as starting points, an energy-switching surface is constructed which is capable of reproducing the whole HDO spectrum from 0 to 35 000 cm − 1 . This PES is used to calculate a line list for HDO which covers infra red, visible and near ultraviolet transitions.